PENGADAAN TANAH UNTUK PEMBANGUNAN INFRASTRUKTUR BERSARANAKAN BANGUN GUNA SERAH - FX. Sumarja (BHUMI: Jurnal Agraria dan Pertanahan, 2014)
Generally the infrastructural development needs space and land. In its process, the role of a private sector may not beneglected as this frequently does not take care of the people’s rights on land. The society, as a subject of the development, shouldhave got a prospeorus living condition. Yet, they were marginalized and regarded as an object of the development. KonsepTheconcept of infrastructural development ,which does not grab people’s right on land, takes care of the living resources, andmaintains the sustainable living situation, would be one of the solutions.Key words: land acquisition, infrastructural development.